The Value Diagnostic of Procalcitonin and Complete Blood Count in Patients with Sepsis due to Community -Acquired Pneumonia. - AL-Banaa, Jaafar Salman Jasim; Kadhum, Najeh Hashem; Rahi, Sattar Jabbar; Alhibaly, Hameed Abdulhasan; Aljanabi, Monqith abdulmohsin (Karbala Journal of Medicine, 2024)
Background :Community-acquired pneumonia (CAP) the acute infection of lung tissue in a patient who has acquired it from the community.The most common bacterial pneumonia complications are sepsis .it is a life-threatening organ dysfunction caused by a deregulated host response to infection . Objective : This research aims to to find potential value diagnostic for Procalcitonin (PCT) and Complete Blood Count (CBC) markers, which could provide diagnostic and prognostic value markers for community -acquired pneumonia and sepsis. Materials and Methods: The samples were (120) participated divided into (20) patients of sepsis due to CAP , (60) patients with bacterial CAP and (40) control were collected blood samples from both males and females patients between the age of (23-95 years) and the average age was (54.9 , 72.5 and 51.4 years) for the three groups in the study. All the samples were diagnosis by doctor specializing in respiratory and chest diseases, at Imam Al-Sadiq Hospital in Babylon Governorate, and a doctor specializing in Internal Medicine at Imam Al-Hussein Medical City in Kerbela Governorate during the period December 2022 to June 2023. the PCT were estimated by using automated a combination of Up-converting Phosphor Technology (UPT) and immunochromatography and CBC results by using automated haematology analyzers Sysmex XN -2000. Results: the results showed high significant differences regarding most investigated parameters (PCT,WBC, Lym, Mono,Gra , Lym % , Mono%, Gra%, HCT and N/L ratio .) at P value < 0.000 expect HGB at P value < 0.002 and PLT / L at P value < 0.001 while PLT there is no significant differences at P value < 0.094 and also showed the PCT, WBC,GRA,GRA % ,N/L ratio and PLT/L ratio were elevated in patients of CAP and sepsis due to CAP compared to control while reduced the results of the LYM, LYM %,HGB and HCT in patients of CAP and sepsis due to CAP compared to control .Conclusion: Our results showed that PCT , WBC , GRA , GRA% ,NLR and PLR were more valuable marker for the diagnosis the patients with CAP and Sepsis due to CAP than other CBC parameters.